Teachers Concerns toward the Integral Reform for Secondary Schools in Mexico - Roger Reyes Osorio Puch; Silvia J. Pech Campos (Universidad Autónoma de Madrid, 2018)
In this research the Concerns Based Adoption Model (CBAM) was used as proposed by Fuller, 1972; George, 1978 y Hall, et al., 1991, in order to identify the main concerns stages in which teachers working in Secondary School level in the Yucatan State were at, where the first phase of the RIES (Integral Reform for Secondary Schools) was implemented. The results of the participating teachers in the first phase shows that 40% (20 Ss), were at the Informational Stage and 72% (36 Ss) of the teachers who did not participate in the first stage were at this level, this shows that more accurate information regarding the reform is needed. On the other hand, a higher concern toward the changes proposed by the SEP (Ministry of Education) was identified, as well as a moderate positive anticipation for success toward the RIES to improve the quality of education in the State of Yucatan, Mexico.